2016
DOI: 10.1111/tid.12476
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and prevalence of positive QuantiFERONTB Gold In‐Tube test in renal transplant candidates

Abstract: Our high prevalence was likely a result of the high number of foreign-born RTC. Half of our small subset of low/intermediate-positive QFT-GIT patients reverted to negative. QFT-GIT-positive patients were more likely to have their LDKT delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
4
1
1
Order By: Relevance
“…Almost 10% of our cohort had a positive QFT‐GIT. Like in our cohort of kidney transplant candidates, we found that positive QFT‐GIT was more common among foreign‐born patients …”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Almost 10% of our cohort had a positive QFT‐GIT. Like in our cohort of kidney transplant candidates, we found that positive QFT‐GIT was more common among foreign‐born patients …”
Section: Discussionsupporting
confidence: 53%
“…Like in our cohort of kidney transplant candidates, we found that positive QFT-GIT was more common among foreign-born patients. 17 In our cohort, eight living donors with positive QFT-GIT with values <1.03 IU/mL were not treated as their repeated QFT-GIT were negative. QFT-GIT value of ≥0.35 < 1 IU/mL has been associated with false positivity in patients with low TB risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S mk ns ve ark. 25 722 renal transplant adayıyla yaptıkları çalışmada bu oranı %16 olarak rapor etm şlerd r. Igar ve ark. 26 137 hastayla yaptıkları çalışmada bu oranı %5,9 olarak bulmuşlardır.…”
unclassified